2021
DOI: 10.1002/rmv.2255
|View full text |Cite
|
Sign up to set email alerts
|

Association of adenovirus 36 infection and obesity; An updated meta‐analysis of community‐based studies

Abstract: As a health problem, obesity has several risk factors; it has been suggested that human adenovirus type 36 (HAdV-36) infections may possibly be associated with obesity. This updated meta-analysis was designed and conducted with an emphasis on articles published from 2015 to 2020. The PubMed, Web of Science, and Scopus databases were searched up to 1 December 2020. Overall, pooled prevalence and odds ratio of antibodies against HAdV-36 in people with obesity and controls was assessed among different ages. Case-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
(199 reference statements)
2
12
0
Order By: Relevance
“…In agreement with previous studies, [13][14][15]21 our results strengthen the need to continue studying the molecular mechanisms involved in infectobesity, particularly the host-pathogen relationship, in accordance with other authors. 39,43 In light of our results, we consider it important to reconsider whether Ad36 infection is truly a low-risk factor for developing obesity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies, [13][14][15]21 our results strengthen the need to continue studying the molecular mechanisms involved in infectobesity, particularly the host-pathogen relationship, in accordance with other authors. 39,43 In light of our results, we consider it important to reconsider whether Ad36 infection is truly a low-risk factor for developing obesity.…”
Section: Discussionsupporting
confidence: 93%
“…12 Some recent systematic reviews have found strong evidence suggesting a positive association between Ad36 infection and obesity. [13][14][15] Ad36 is the only virus that has been related to obesity in humans, 6 assuming that the presence of peripheral IgGs against Ad36 as indirect evidence of infection. 13,16,17 Since the description of Ad36 in the 1980s when the obesity epidemic increased in such a way that in many countries it was the main health problem, the term infectobesity (obesity associated with microorganisms and changes in metabolic functions) was adopted; it includes both bacterial and viral agents.…”
mentioning
confidence: 99%
“…Some previous comprehensive studies have measured the prevalence of viruses and their association with non-communicable disease especially gastrointestinal complications. [194][195][196][197][198] According to our results, the overall pooled prevalence of SaV infection among children with AGE 3.4%. Also, analysis of 20 included case-control studies showed a higher prevalence of SaV infection is found in the case of children with AGE (7.5%) than healthy or asymptomatic controls (4.5%).…”
Section: Discussionmentioning
confidence: 52%
“…To the best of our knowledge, the current study is the first systematic review and meta‐analysis on the global prevalence and genotyping of SaV. Some previous comprehensive studies have measured the prevalence of viruses and their association with non‐communicable disease especially gastrointestinal complications 194–198 . According to our results, the overall pooled prevalence of SaV infection among children with AGE 3.4%.…”
Section: Discussionmentioning
confidence: 72%
“…Some pathogens are involved in the development of AGE, of which, viruses are responsible for about 70% of cases 2,3 . Rotavirus (RoV), Norovirus (NoV), Enteric Adenovirus (EAdV), Human Astrovirus (HAstV), and Sapovirus (SaV) are the most well‐known viruses in the development of AGE 1,4,5 . In addition, some emerging viruses were recently isolated from faecal samples of patients with AGE.…”
Section: Introductionmentioning
confidence: 99%